Pengaruh Edukasi Senam Kaki Diabetes Mellitus Berbahasa Tetum Terhadap Sirkulasi Ekstremitas Bawah Dan Kadar Gula Darah Sewaktu Di Centru Saude Comoro, Dili, Timor Leste. - Carmelita Barros; Fitri Arofiati (Fakultas Ilmu Kesehatan, 2020)
ABSTRACT Diabetes mellitus (DM) in Indonesia is better known as diabetes and in Timor Leste DM known as Ra'an Midar has become a very serious health problem, and is the most common endocrine disease. Diabetes mellitus is a degenerative disease that is characterized by metabolic disorders or pancreatic damage so that the pancreas is unable to produce enough insulin to the maximum so that it can cause insulin deficiency in the body both absolute and relative can increase blood sugar levels or hyperglycemia. Data from the Dili District Health Office in 2018 showed that there were 2690 patients with diabetes mellitus, so that diabetic foot exercises were needed. The purpose of this study was to determine the effect of Tetum Language Diabetes Foot Gymnastic Education on Lower Circulation and Lower Blood Sugar Levels at the Saude Comoro Center, Dili, Timor Leste. Method : using the Pre-Experiment method. Independent variable: Education of Tetum Language Diabetes Foot Gymnastics Education, dependent variable: Circulation of Lower Extremity and Blood Sugar Level at a Time. Population 100 people, sample 28 people, sample technique: simple random, data collection: Examination of blood sugar levels, blood circulation, statistical tests: Wilcoxon Test. Results : Most respondents who had good blood circulation were 15 pre- test (53.6%) and 18 post-test (64.3%). And the majority of respondents whose blood sugar levels were good were 14 people pre-test (50.0%) and 20 people post test (71.4%). Based on the results of statistical tests using the Wilcoxon Signed Rank Test, the value of blood circulation is a significant level of 0.005 and the blood sugar level is at a significant level of 0,000. Conclusion : Conclusion there is the influence of Education on Tetun Language Diabetes Foot Gymnastics on Lower Extracurricular Circulation and Blood Sugar Levels At the Saude Comoro Center, Dili, Timor Leste. Keyword: Leg exercise, lower extremity bloodd circulation, Blood sugar levels, Diabetes mellitus.